How Does the Negative Impact of an Athlete's Reputational Crisis Spill Over to Endorsed and Competing Brands? The Moderating Effects of Consumer Knowledge. (June 2019) - Sato, Shintaro; Ko, Yong Jae; Chang, Yonghwan; Kay, Mark
Despite some of the recent examinations of an athlete's reputational crisis (ARC), their negative spillover effects on endorsed and competing brands have been overlooked. The purpose of this study is to investigate the relationships between perceived severity, athlete endorser credibility (i.e., incompetence, untrustworthiness), and attitudes towards endorsed and competing brands. To enhance theoretical understanding of the phenomenon, the moderating role of consumer knowledge was also tested. Participants were recruited from Amazon Mechanical Turk ( N = 339 ). A multigroup structural equation model was employed to test the hypothesized model. Results indicated that the severity of an ARC is associated with the perceived incompetence and untrustworthiness of focal athletes. Perceived incompetence is associated with negative evaluation of an endorsed brand. Furthermore, this impact is significantly stronger for consumers with greater knowledge of the athletes than those who are less knowledgeable. Interestingly, competitor brands received negative impact indirectly from the athlete endorsers' incompetence. This spillover effect is also manifested differently depending on the level of consumer knowledge.